(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The term social media refers to a group of online communication channels devoted tofostering participation, engagement, the exchange of ideas, and collaboration among members of acertain community. This review’s overarching goal is to provide specifics on the societal effects ofsocial media. Previous research shown that social media can have both beneficial and negative effectson individuals. The positives outcomes are better socialization and communication increasededucational possibilities and better access to health information. Social media can have a negativeimpact on society in the form of depression, anxiety, bullying, terrorism, or other criminal activity.